2022
DOI: 10.3389/fimmu.2022.952040
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages: A communication network linking Porphyromonas gingivalis infection and associated systemic diseases

Abstract: Porphyromonas gingivalis (P. gingivalis) is a Gram-negative anaerobic pathogen that is involved in the pathogenesis of periodontitis and systemic diseases. P. gingivalis has recently been detected in rheumatoid arthritis (RA), cardiovascular disease, and tumors, as well as Alzheimer’s disease (AD), and the presence of P. gingivalis in these diseases are correlated with poor prognosis. Macrophages are major innate immune cells which modulate immune responses against pathogens, however, multiple bacteria have ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 105 publications
0
13
0
1
Order By: Relevance
“…Macrophage polarization manifests various functions in anti‐infection and inflammation regulation because the balance between pro‐ (M1) and anti‐inflammatory (M2) macrophages is crucial for maintaining periodontal homeostasis. [ 4 ] Nonetheless, chronic and uncontrollable infection results in prolonged M1 polarization instead of M2 polarization of macrophages, suggesting a delayed transition from the anti‐infection to the anti‐inflammation stage. This could lead to the failure of tissue reconstruction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophage polarization manifests various functions in anti‐infection and inflammation regulation because the balance between pro‐ (M1) and anti‐inflammatory (M2) macrophages is crucial for maintaining periodontal homeostasis. [ 4 ] Nonetheless, chronic and uncontrollable infection results in prolonged M1 polarization instead of M2 polarization of macrophages, suggesting a delayed transition from the anti‐infection to the anti‐inflammation stage. This could lead to the failure of tissue reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulative evidence has shown the importance of macrophages in defending periodontal infection and launching regeneration. [4,36] Host inflammation responds to bacterial invasion; however, sustained and chronic infection results in uncontrollable inflammatory effects that could compromise periodontal homeostasis. [31,37] Pathogens like P. gingivalis pull the danger alarm as pathogen-associated molecular patterns (PAMPs), which induce the pyroptosis of macrophages via NLRP3 inflammasome activation.…”
Section: Pgm/cpl@ni Effectively Attenuated P Gingivalis-induced Nlrp3...mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides promoting the maturation of DCs, LPS is also known to stimulate the M1 polarization of macrophages, which will facilitate remodeling the antitumor immune microenvironment. 42,43 The results shown in Fig. 2B revealed that DMVs from attenuated Pg and PBAE/IR780@DMV both contained approximately 50% of the LPS content of DMVs from Pg.…”
Section: In Vitro Antitumor Immunity Induced By Pbae/ Ir780@dmv Upon ...mentioning
confidence: 90%
“…P. gingivalis , which survives in macrophages, induces inflammatory vesicle activation and M1-type polarization in macrophages ( 155 ). Animal studies have shown that oral inoculation of P. gingivalis can activate NLRP3 inflammasomes in macrophages in AS plaques in a gingipains-independent manner, promote the release of IL-1β and TNF-α, and accelerate AS progression ( 47 , 148 ).…”
Section: Immune Mechanism Of P Gingivalis To Promo...mentioning
confidence: 99%